Mechanism of Electronegativity Heterojunction of Nanometer Amorphous-Boron on Crystalline Silicon: An Overview - Paolo Sberna; Piet X. Fang; Changming Fang; Stoyan Nihtianov (Crystals, 2021)
The discovery of the extremely shallow amorphous boron-crystalline silicon heterojunction occurred during the development of highly sensitive, hard and robust detectors for low-penetration-depth ionizing radiation, such as ultraviolet photons and low-energy electrons (below 1 keV). For many years it was believed that the junction created by the chemical vapor deposition of amorphous boron on n-type crystalline silicon was a shallow p-n junction, although experimental results could not provide evidence for such a conclusion. Only recently, quantum-mechanics based modelling revealed the unique nature and the formation mechanism of this new junction. Here, we review the initiation and the history of understanding the a-B/c-Si interface (henceforth called the “boron-silicon junction”), as well as its importance for the microelectronics industry, followed by the scientific perception of the new junctions. Future developments and possible research directions are also discussed.